2017
DOI: 10.4014/jmb.1701.01073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Synergistic Effect of Mixed Cultures of White-Rot Fungus Pleurotus ostreatus and Biosurfactant-Producing Bacteria on DDT Biodegradation

Abstract: DDT (1,1,1-trichloro-2,2-(4-chlorophenyl) ethane) is one of the organic synthetic pesticides that has many negative effects for human health and the environment. The purpose of this study was to investigate the synergistic effect of mixed cutures of white-rot fungus, , and biosurfactant-producing bacteria, and , on DDT biodegradation. Bacteria were added into the culture (mycelial wet weight on average by 8.53 g) in concentrations of 1, 3, 5, and 10 ml (1 ml ≈ 1.25 × 10 bacteria cells/ml culture). DDT was degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 62 publications
1
28
1
Order By: Relevance
“…The DDT degradation by co-cultures of fungi and bacteria has been reported previously. The synergistic co-cultures P. aeruginosa -P. ostreatus [17], P. brevispora -B. subtilis [19], G. lingzhi -B. subtilis [21] were previously reported as having degradation efficiency of 75~86%. In the cases of brown-rot fungus, Sariwati et al [43] and Sariwati and Purnomo [44] reported that the addition of B. subtilis and P. aeruginosa increased DDT degradation by Fomitopsis pinicola, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DDT degradation by co-cultures of fungi and bacteria has been reported previously. The synergistic co-cultures P. aeruginosa -P. ostreatus [17], P. brevispora -B. subtilis [19], G. lingzhi -B. subtilis [21] were previously reported as having degradation efficiency of 75~86%. In the cases of brown-rot fungus, Sariwati et al [43] and Sariwati and Purnomo [44] reported that the addition of B. subtilis and P. aeruginosa increased DDT degradation by Fomitopsis pinicola, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has the ability to weaken environmental contaminants such as polychlorinated dioxins [7], polychlorinated biphenyls [8], cyclodiene insecticide [9], industrial dye effluents, munitions waste, pesticides, herbicides, and petroleum hydrocarbons [10][11][12][13]. Some of the WRF that possess the capability to degrade DDT include Phanerochaete chrysosporium, Trametes versicolor [14], Pleurotus ostreatus [15][16][17], Pleurotus florida, Pleurotus sajorcaju, Pleurotus eryngii [18], Phlebia lindtneri and Phlebia brevispora [19,20], and Ganoderma lingzhi [21] as well as some brown-rot fungi [22][23][24]. Besides, Arisoy [18] also reported that P. eryngii could degrade DDT approximately 66% over a 20-day incubation period in mineral medium.…”
Section: Introductionmentioning
confidence: 99%
“…Bioaugmentation with the glycoconjugate-producing bacteria also proved to be an efficient technique for the remediation of pesticides. The α and β isomers of the endosulfan degraded by up to 82 % in the presence of glycocnjugates having biosurfactant properties [151,152].…”
Section: Glycoconjugates In Pesticide Degradationmentioning
confidence: 99%
“…Besides, B. subtilis can be mixed with some brown-rot fungi (BRF), such as Gloephyllum trabeum, Daedalea dickinsii, and Fomitopsis pinicola as well as white-rot fungi (WRF) such as Pleurotus ostreatus, Pleurotus eryngii, and Ganoderma lingzhi. Mixed culture B. subtilis and BRF had been reported to enhance DDT degradation as well as dyes decolorization [29][30][31][32].…”
Section: Analysis Of Degradation Products (Gc-ms)mentioning
confidence: 99%